Pemanfaatan Kitosan Tersambung Silang dengan Tripolifosfat sebagai Eksipien Gel Ikan Haruan (Channa Striatus) - DINA RAHMAWANTY; EFFIONORA ANWAR; ANTON BAHTIAR (Fakultas Farmasi Universitas Pancasila, 2015)
Meat of snakehead fish (Channa striatus) has been reported can be used for wound healing because contains proteins, essential amino acids, lipid and fatty acids that inuenced wound healing process. The present study was performed in order to formulate gels contain meat powders of snakehead fish for wound healing. The formulas were used 1 g (formula 1) and 2 g (formula 2) meat powder of snakehead fish as an active ingredient. Meat powder of snakehead fish have been made nanosuspension use ionic gelation method with chitosan and sodium tripolyphosphate and formulated to gel form using HPMC as gelling agent. Suspenses have been physicochemical charactheried. The results showed that suspenses (formula 1 and formula 2) have particle sie in range of 41.665.5 nm and 41.2.1 nm respectively polidispersity inde of 0.512 and 0.456 respectively eta potential ()2.15 m and ()2.35 m respectively both of formulas have spherical particles.